Emerging Trends and Advanced Technologies for Computational Intelligence Extended and Selected Results from the Science and Information Conference 2015 - Chen, Liming; Kapoor, Supriya; Bhatia, Rahul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is a collection of extended chapters from the selected papers that were published in the proceedings of Science and Information (SAI) Conference 2015. It contains twenty-one chapters in the field of Computational Intelligence, which received highly recommended feedback during SAI Conference 2015 review process. During the three-day event 260 scientists, technology developers, young researcher including PhD students, and industrial practitioners from 56 countries have engaged intensively in presentations, demonstrations, open panel sessions and informal discussions. .
A Plantar Inclinometer Based Approach to Fall Detection in Open Environments -- Using Fuzzy Evidential Reasoning for Multiple Assessment Fusion in Spondylarthropathic Patient Self-Management -- Rescue System with Sensor Network for Vital Sign Monitoring and Rescue Simulations by Taking into Account Triage with Measured Vital Signs -- An Approach for Detecting Traffic Events using Social Media -- Applying Supervised & Unsupervised Learning Techniques on Dental Patients' Records -- Technology in Primary Schools: Teachers' Perspective towards the Use of Mobile Technology in Children Education -- Designing, Implementing and Testing an Automated Trading Strategy Based on Dynamic Bayesian Networks, the Limit Order Book Information and the Random Entry Protocol -- An Adaptive Multi Agent Service Discovery for Peer to Peer Cloud Services -- Modelling and Detection of User Activity Patterns for Energy Saving in Buildings -- e QoS using PSO in Fixed WiMAXNetworks -- Colour-Preserving Contrast Enhancement Algorithm for Images -- Sequential Pattern Discovery for Weather Prediction Problem -- A Class-based Strategy to User Behavior Modeling in Recommender Systems -- Feature Correspondence in Low Quality CCTV Videos -- Automatic Detection and Severity Assessment of Crop Diseases using Image Pattern Recognition -- Image Complexity and Visual Working Memory Capacity -- Immersive Brain Entrainment in Virtual Worlds: Actualizing Meditative States -- A Real-Time Stereo Vision Based Obstacle Detection -- Depth and Thermal Image Fusion for Human Detection with Occlusion Handling under Poor Illumination from Mobile Robot -- Exploiting the Retinal Vascular Geometry in Identifying the Progression to Diabetic Retinopathy Using Penalized Logistic Regression and Random Forests -- A New Method for Improving the Detection Capability of RADAR in the Presence ofNoise. .
Keywords: Computational intelligence; Artificial intelligence; Computer networks .; Computational Intelligence; Artificial Intelligence; Computer Communication Networks